2021
DOI: 10.1111/psyp.13935
|View full text |Cite
|
Sign up to set email alerts
|

The cumulative effect of positive and negative feedback on emotional experience

Abstract: The cumulative effect of positive or negative feedback on subsequent emotional experiences remains unclear. Elucidating this effect could help individuals to better understand and accept the change in emotional experience, irrespective of when they or others receive consecutive positive or negative feedback. This study aimed to examine this effect on 37 participants using self-reported pleasantness and event-related potential data as indicators. After completing each trial, the participants received predetermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Taken together, these results support the notion that the FRN functionally reflects a mechanism that evaluates whether an outcome meets the expectations (Miltner et al, 1997;Simons, 2010;Potts, 2011;Koban and Pourtois, 2014). However, the P3 and later LPP components are more sensitive to outcome evaluation that is dependent on both motivational aspects and more top-down controlled processing (e.g., attentional allocation and memory update processes; Yeung and Sanfey, 2004;Wu and Zhou, 2009;Bublatzky et al, 2020a;Ming et al, 2021). Regarding the neural structures involved, LORETA source estimations of FRN, P3, and LPP feedback effects confirm previous imaging research (see Figure 5) that identified the anterior cingulate cortex and medial frontal gyrus as key structures involved in behavior monitoring and feedback processing (e.g., Gehring and Willoughby, 2002;Kringelbach and Rolls, 2003;Potts, 2011;Gläscher et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Taken together, these results support the notion that the FRN functionally reflects a mechanism that evaluates whether an outcome meets the expectations (Miltner et al, 1997;Simons, 2010;Potts, 2011;Koban and Pourtois, 2014). However, the P3 and later LPP components are more sensitive to outcome evaluation that is dependent on both motivational aspects and more top-down controlled processing (e.g., attentional allocation and memory update processes; Yeung and Sanfey, 2004;Wu and Zhou, 2009;Bublatzky et al, 2020a;Ming et al, 2021). Regarding the neural structures involved, LORETA source estimations of FRN, P3, and LPP feedback effects confirm previous imaging research (see Figure 5) that identified the anterior cingulate cortex and medial frontal gyrus as key structures involved in behavior monitoring and feedback processing (e.g., Gehring and Willoughby, 2002;Kringelbach and Rolls, 2003;Potts, 2011;Gläscher et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…Here, the motivational relevance of negative feedback indicates the need to adjust behavior, irrespective of contextual settings. Consistent with this reasoning, numerous previous studies showed a particularly pronounced LPP amplitude for negative information [for reviews see Schupp et al (2006) and Schindler and Bublatzky (2020)], which has been associated with defensive motivational states, action-related processing, and psychophysiological response priming (e.g., withdrawal or avoidance behaviors; Löw et al, 2008;Bublatzky and Schupp, 2012;Ming et al, 2021). Faithful to this motivational relevance, threat-enhanced LPP amplitudes were observed only at the onset of the threat context but not at the onset of feedback (which was not threat-predictive) within a threatening context.…”
Section: Discussionmentioning
confidence: 58%
“…Overall this is perhaps an unsurprising finding measured within the body of research surrounding anxiety, interpretation bias and ambiguous information processing (Beard & Amir, 2008;Heitmann et al, 2014). Conversely, given the importance of feedback valance in the stimulus of emotions (Ming et al, 2021), there is perhaps further cause to address the complexity and diversity of the types of feedback within the feedback metaphor. Considering the participants experiences in relation to rumination and thinking 'what if' minimising unnecessarily ambiguity in the feedback exchange could arguably influence their total experience.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that the valance of feedback influences the emotional experience of the receiver (Ming et al, 2021). Evidenced in both academic and business literature, the diverse types of feedback have now exceeded the more traditional labels of positive and negative to also include reinforcement, corrective, coaching, appreciation, 360° and forward feedback (Baker, 2022;Mesch et al, 1994;Valamis, 2021;Wisniewski et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%